Investigation of a potential scintigraphic marker of apoptosis: radioiodinated Z-Val-Ala-DL-Asp(O-methyl)-fluoromethyl ketone - Haberkorn, Uwe; Kinscherf, Ralf; Krammer, Peter H.; Mier, Walter; Eisenhut, Michael (Nuclear medicine and biology, 2001)
The imaging of apoptosis represents an attractive diagnostic goal in the area of tumor therapy, degenerative diseases and organ transplantation. Since caspases play a key role during the early period of the intracellular signal cascade of cells undergoing apoptosis we considered benzyloxycarbonyl-Val-Ala-DL-Asp(O-methyl)-fluoromethyl ketone [Z-VAD-fmk], a pan-caspase inhibitor, as a potential apoptosis imaging agent. Applying the Tl(TFA)3/[131I]iodide method Z-VAD-fmk was successfully labeled at the benzyloxycarbonyl protecting group. The success of radioiodination, however, depended on the presence of carrier iodide resulting in specific radioactivities of 2.6 GBq/μmol and the formation of a mixture of the 2- and 4-iodophenyl derivative (61%) which could not be separated by HPLC. Uptake measurements were performed with Morris hepatoma cells (MH3924Atk8) which showed expression of the Herpes Simplex Virus thymidine kinase (HSVtk) gene. Apoptosis was induced by treatment of the cells with 25 μM ganciclovir. The TUNEL assay revealed 1.3 ±0.3 and 23 ±1.1% apoptotic cells immediately and 24 h after therapy, respectively. A two-fold increase of [131I]IZ-VAD-fmk uptake was found at the end of treatment with the HSVtk/suicide system which constantly remained elevated for the following 4 hours. The slow cellular influx and lack of uptake saturation of [131I]IZ-VAD-fmk are evidence for simple diffusion as transport mechanism. In addition, the absolute cellular uptake of [131I]IZ-VAD-fmk was found to be low. This quality was related to the rather high lipophilicity of [131I]IZ-VAD-fmk causing unspecific binding to macromolecules in the medium. Instead of using an inhibitor, synthetic caspase substrates are currently investigated which may accumulate in the apoptotic cell by metabolic trapping thereby enhancing the imaging signal.